The efficacy of randomised controlled trials of cognitive behaviour therapy for perfectionism: a systematic review and meta-analysis. Issue 2 (4th March 2022) - Galloway, Ricky; Watson, Hunna; Greene, Danyelle; Shafran, Roz; Egan, Sarah J.
ABSTRACT: Perfectionism is a transdiagnostic process across anxiety, depression, and eating disorders. The aim of this systematic review was to examine the efficacy of self-help and face to face CBT for perfectionism in reducing perfectionism and anxiety, depression, and eating disorders. A total of 15 randomised controlled trials of CBT for perfectionism were identified ( N = 912 participants; mean pooled age = 23 years) which met inclusion criteria. There were medium or large effect sizes found on perfectionism measures; personal standards ( g = 0.57, 95% CI = 0.43–0.72), concern over mistakes ( g = 0.89, 95% CI = 0.71–1.08) and clinical perfectionism ( g = 0.87, 95% CI = 0.70–1.04). There were medium effects for symptoms of eating disorders ( g = 0.61, 95% CI = 0.36–0.87) and depression ( g = 0.60, 95% CI = 0.28–0.91), and a small-medium effect on anxiety ( g = 0.42, 95% CI = 0.21–0.62). There was no publication bias found. Limitations included the small number of trials included and lack of active treatment comparisons. Results suggested that CBT for perfectionism is efficacious in reducing perfectionism and symptoms of depression, anxiety and eating disorders. Future research should examine comparisons of CBT for perfectionism with other psychological treatments.